2021
DOI: 10.3390/ma14061345
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Water and Road Salt with Anti-Caking Agent on the Stiffness of Select Mixes Used for the Road Surface

Abstract: An original experimental method was used to investigate the influence of water and road salt with anti-caking agent on the material used in pavement construction layers. This method allowed for monitoring material changes resulting from the influence of water and road salt with anti-caking agent over time. The experiment used five different mineral road mixes, which were soaked separately in water and brine for two time intervals (2 days and 21 days). Then, each sample of the mix was subjected to tests of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…An original experimental method was used to investigate the influence of water and road salt with an anti-caking agent on the material used in pavement construction layers [ 58 ]. This method allowed the monitoring of material changes resulting from the influence of water and road salt with an anti-caking agent over time.…”
Section: Description Of the Articles Presented In The Issuementioning
confidence: 99%
See 1 more Smart Citation
“…An original experimental method was used to investigate the influence of water and road salt with an anti-caking agent on the material used in pavement construction layers [ 58 ]. This method allowed the monitoring of material changes resulting from the influence of water and road salt with an anti-caking agent over time.…”
Section: Description Of the Articles Presented In The Issuementioning
confidence: 99%
“…Based on the measurements of the stiffness modulus and absorption, the correlations of the mass change and the value of the stiffness modulus were determined, which may be useful in estimating the sensitivity of mixes to the use of winter maintenance agents, e.g., road salt with an anti-caking agent (sodium chloride). It was found that the greatest changes occur with mixes intended for base course layers (mineral cement mix with foamed asphalt (MCAS) and mineral-cement-emulsion mixes (MCE)), and that the smallest changes occur for mixes containing highly modified asphalt (HIMA) [ 58 ].…”
Section: Description Of the Articles Presented In The Issuementioning
confidence: 99%
“…In addition to the anions and cations of salts, the presence of other compounds related to anti-caking agents is a concern in runoff water containing road de-icing salts. Anti-caking agents are used to prevent salt agglomeration when applied on roads (Mackiewicz & Mączka, 2021). In particular, a brine solution forms between salt crystals when the relative atmospheric humidity exceeds 70-75%.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years various researchers have carried out experimentation on the stiffness properties of asphalt mixtures [10][11][12]. The effect of mixture stiffness on the fatigue life of asphalt pavements was investigated [13][14][15].…”
Section: Introductionmentioning
confidence: 99%